2004
DOI: 10.1093/eurpub/14.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Imprints on the consciousness: The impact on Palestinian civilians of the Israeli Army invasion of West Bank towns

Abstract: civilians inevitably suffer during conflict and war from destruction of the community infrastructure and from personal stress due to disruption of services and the non-fulfilment of basic human needs. In contradistinction to standard damage assessments that focus on collective physical damage, this scale provides richer information on the needs of civilians in conflict-torn areas, and can assist aid workers in the efficient deployment of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…A rich body of literature documents the impact of chronic conflict, violence, humiliation, and imprisonment on Palestinian social institutions, family function, personal coping mechanisms, and development of social support networks (see Khamis 1993;Punamäki et al 2002Punamäki et al , 2005Kanninen et al 2003;Giacaman et al 2004;Roy 2004;Peltonen et al 2010;Hobfall et al 2012 for examples). It should come as no surprise that levels of stress, anxiety, and trauma symptomology are elevated in Palestinian populations living in both West Bank and Gaza Strip communities who are exposed to armed conflict and violence (de Jong et al 2003;Giacaman et al 2007;Khamis 2008;Qouta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A rich body of literature documents the impact of chronic conflict, violence, humiliation, and imprisonment on Palestinian social institutions, family function, personal coping mechanisms, and development of social support networks (see Khamis 1993;Punamäki et al 2002Punamäki et al , 2005Kanninen et al 2003;Giacaman et al 2004;Roy 2004;Peltonen et al 2010;Hobfall et al 2012 for examples). It should come as no surprise that levels of stress, anxiety, and trauma symptomology are elevated in Palestinian populations living in both West Bank and Gaza Strip communities who are exposed to armed conflict and violence (de Jong et al 2003;Giacaman et al 2007;Khamis 2008;Qouta et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that the Palestinian population was psychologically and socially affected by the ongoing political violence (Giacaman, Husseini, Gordon, & Awartani, 2004). Al-Ashhab (2005) for example, reported that about two-thirds of Palestinians feel insecure, a feeling reinforced by the growing occurrences of domestic violence.…”
mentioning
confidence: 99%
“…19 Yet despite these violent conditions, ICPH researchers embarked on documenting the consequences of incursions and curfews for the social and health-related quality of life of civilians during this period. 20 Simultaneously with our fieldwork, we put in place public health interventions such as operating hotlines to link the population to medication donors, distributing food whenever curfew was lifted for a couple of hours every few days, linking patients to ambulances, and even teaching our students remotely through the use of the internet, telephones, and faxes so that they could complete the semester despite the odds. 21 By the time of the Second Intifada, our ability to access international research had become much improved as BZU's library connected us to various types of international literature search engines.…”
mentioning
confidence: 99%